(untitled) (International Journal of Studies in Nursing, 2022)
Worldwide, cervical cancer (CC) is the fourth most common cancer among women. Approximately 90% of cervical cancer cases occur in resource limited countries. Malawi is one of the developing countries with the highest incidence (ASR 67.9 per 100,000) of cc and the highest number of deaths (ASR 51.5 per 100,000) from cervical cancer in the world. More than 80% of Malawian women diagnosed with CC are at the inoperable cancer stage and suffer from co-infection with HIV. The purpose of this situation-specific theory guided study was to examine the cervical cancer screening status and factors affecting the screening status among Malawian women living with HIV infection aged 18-50 from HIV support groups in Malawi. A two stage proportionate stratified cluster random sampling method was used to select 291 respondents. The findings indicated that the prevalence of cervical cancer screening rate was 27.8%; and women had a high knowledge level and had a positive attitude towards cervical cancer screening. Despite a high knowledge level and positive attitude regarding screening, the cervical cancer screening rate was still low. The factors independently associated with cervical cancer screening in HIV positive women were: employment, OR = 6.37 (95% CI: 1.32, 30.80), knowledge OR =1.11 (95% CI: 1.03,